Dinamika Kajian Pendidikan Bahasa Arab Dalam Sripsi Mahasiswa Program Studi Pendidikan Bahasa Arab Antara Tahun 2010-2014 Fakultas Ilmu Tarbiyah Dan Keguruan IAIN Surakarta - Ghofur, Abdul (Sekolah Tinggi Agama Islam (STAIN)Curup, 2017)
This research departs from academic anxiety, the thesis is only used as an annual ritual for the graduation requirements of students, regardless of competence standards, methodological, and actuality issues about education, especially ignored Arabic. In this case thesis student of Arabic Education Study Program (PBA) IAIN Surakarta year 201-2015. The few questions that will be answered in this study are: what are the Arabic educational clusters that have been studied; What percentage, which clusters are already saturated and need to be abandoned to avoid repetition; What clusters are still open opportunities to serve as a topic of study in the future; How its adaptability to the new educational issues being in the community, and what are the methodological problems that are often found. This study includes literary because the data and primary sources are derived from written materials derived from the thesis of students Prodi PBA FITK IAIN Surakarta 2010-2014. This research is descriptive qualitative, data collection using documentation technique. The written data collected and categorized and then analyzed inductively by content analysis method (content analysis). Data analysis technique is an interactive analysis model, namely: data reduction data, and drawing conclusions. The result of this research shows that from 98 thesis amount,